The snow angel - Weyn, Suzanne ([S.l.] : Troll, 1997)
Molly and her friends have made a snow angel in the woods that is so beautiful, people are coming from miles around to see it. When a strange boy comes to live with Molly's family following his tragic riding accident, Molly wants to find a way to reach him. Can an angel help her break through his silence?
K
b
b
Keywords: Angels -- Fiction; Friendship -- Fiction; Children's stories